2018
DOI: 10.1037/neu0000423
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury history is associated with an earlier age of dementia onset in autopsy-confirmed Alzheimer’s disease.

Abstract: History of TBI with reported LOC appears to be a risk factor for earlier AD onset. This is the first study to use autopsy-confirmed cases, supporting previous investigations that used clinical criteria for the diagnosis of AD. Further investigation as to possible underlying mechanisms of association is needed. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 41 publications
(72 reference statements)
3
69
0
Order By: Relevance
“…This mirrors a general trend towards greater post-TBI dementia risk in men in the observational studies. A further study of autopsy-confirmed AD cases reported an earlier symptom onset and dementia diagnosis of 3.6 years in patients with prior TBI 16…”
Section: How Common Is Dementia After Head Injury?mentioning
confidence: 93%
“…This mirrors a general trend towards greater post-TBI dementia risk in men in the observational studies. A further study of autopsy-confirmed AD cases reported an earlier symptom onset and dementia diagnosis of 3.6 years in patients with prior TBI 16…”
Section: How Common Is Dementia After Head Injury?mentioning
confidence: 93%
“…The relationship between Alzheimer's disease (AD) and CTE remains somewhat enigmatic. Both tauopathies share a series of culprit tau phosphorylation sites (Katsumoto et al, 2019) and TBI (but not necessarily rmTBI) is a risk factor for AD (Nemetz et al, 1999;Schaffert et al, 2018). Additionally, a mixed CTE/AD phenotype has been reported (Kanaan et al, 2016), leading some researchers to question whether CTE can eventually lead to AD (Katsumoto et al, 2019).…”
Section: Comorbidities and Neuropathologymentioning
confidence: 99%
“…While immediate cognitive impairment is a well‐known adverse outcome of TBI, the long‐term consequences at older age are less consistent. On one hand, there is existing evidence to support an association between moderate to severe TBI and increased dementia risk 10‐17 or Alzheimer's disease (AD) risk 10,18‐22 . On the other hand, some other recent studies showed no difference in dementia incidence, 23‐28 AD dementia, 23,24,29 or AD biomarkers or neuropathological measures 23,28,30 between individuals with and without a history of moderate to severe TBI.…”
Section: Introductionmentioning
confidence: 99%